DIGITALISASI UMKM DI DESA DARMAJI GUNA MENCIPTAKAN WIRAUSAHAWAN CAKAP DIGITAL - Andikasari, Devi; Fadli, Sofiansyah; Mutawalli, Lalu; Zaen, Mohammad Taufan Asri; Tantoni, Ahmad (CV. Aksara Global Akademia, 2025)
Darmji Village is one of the villages that has residents who produce printed handicrafts and various types of ready-to-pack food. The people in the village are able to produce thousands of handicraft products within one month, but the problems faced by the people there are that they are not competent enough to digitalize to promote their products worldwide. , so that I, fromSTMIK LOMBOKstudents, took the initiative to conduct community service training in the village to help the community understand how to use social media to increase the selling value of their products so that from this they can increase the income of the people in Darmaji village, the method I use in this service training is the method Observations, interviews, socialization and training, so that at the end of the activity we get an increase in graphics from 0% to 53% of the knowledge that I convey to the public can be absorbed and applied properly